THE IMPACT OF PRICE PERCEPTION, SALES PROMOTION, CUSTOMER SATISFACTION OF MILLENNIAL CHEESE ROLLING CHILDREN - Hasugian, Buyung Solihin; Sari, Ayu Wulanda (Universitas Dharmawangsa Medan, 2023)
ABSTRACTÂ The pandemic of the COVID-19 outbreak has impacted a global crisis that puts small and even medium-sized in serious trouble. Small and medium-sized have to respond effectively to the crisis. Small and medium-sized are seeking to take advantage of a variety of digital technologies that are developing today. Business transformation using online media will have a good impact in marketing a product from a small even medium-sized enterprise. Digital media is used among social media, marketplace, Google business, and so on. With the use of online media, he hopes to make product marketing reach wider and increase the sales of a product. The research method used is a qualitative method with a descriptive approach through the study of libraries by conducting research through several actual and factual sources.Â Keywords: product marketing, digital media, millennials